Trends in the Uses of Spirulina Microalga: A mini-review - Aondohemba Samuel Nege; Endang Dewi Masithah; Junaidi Khotib (Jurnal Ilmiah Perikanan dan Kelautan)
Highlights • Trends in the uses of Spirulina over different decades were critically examined • Findings from surveyed literature indicated that Spirulina utilization was mainly focused on its food and feed potential before the last 20-30 years • The review observed that research focused on the health and pharmaceutical uses, biofertilizer, bioplastic, cosmetic, bioenergy and pollution control applications of Spirulina are trends that sprouted out within the last 20-25 years. • The review has successfully compiled numerous uses of Spirulina microalga for easy readership by readers since many studies have been performed on the uses Spirulina but reviews of this type spanning through different beneficial aspects of  Spirulina are still scarce. Hence, this review fills such gap.